The Influencing Factors of the Intention to Purchase through Mobile Shopping Apps: A Quantitative Study in Malaysia - Jayanty KUPPUSAMY; CHIN Han Min (Communications of International Proceedings, 2024)
Mobile shopping technology enabled shoppers to shop through the mobile shopping apps. The Covid 19 contributed to the growth of mobile shopping. This is mainly due to the restriction in movement causing people to use mobile shopping apps to purchase product or services. The trend continued after the pandemic, and more mobile shopping apps has been established indicating a growing market. This signifies the importance of this mode of shopping. Although there were studies done on purchase intention through mobile apps, nevertheless, it still limited specifically in the Malaysian context. This indicated a gap and thus, the current study aims to determine the influencing factors of intention to purchase using mobile shopping apps. The factors considered in this study include convenience, usability, mobile application quality, service quality and trust. The respondents consist of adults. The total number of respondents of the study is around one hundred and eighty respondents. Sampling method is through purposive sampling. Data collection is done using online questionnaire. The multiple regression analysis revealed that convenience, usability, and service quality are predictors of the intention to purchase. Therefore, businesses should put focus on these factors to motivate potential buyers to purchase and increase the businesses sales and profitability.
Keywords: convenience; usability; service quality; trust; intention to purchase